Risk identification in managing small and medium-sized enterprises in Poland - Kokot-Stępień, Patrycja (Ekonomia i Prawo. Economics and Law, 2023)
Motivation: When running a business in the form of an enterprise, we agree to take the associated risk. The ubiquitous uncertainty about the future of enterprises, especially from the SME sector, makes risk management more and more important, which includes several successive stages. One of the most important is risk identification. Its purpose is relatively early detection of possible threats that, if they occur, will affect the company and its goals. Knowledge of the factors that may disrupt the functioning of an entity, especially a small and medium one, is the foundation in the approach to the issue of risk accompanying business activity. Properly conducted risk identification should cover all levels of the company’s operation and its relations with the environment. Aim: The article will isolate events, the occurrence of which small and medium-sized entrepreneurs fear the most. The aim of this article is to develop a register of risk sources for SMEs, and to identify the risks that pose the greatest threat to the operation of SMEs. Moreover, the level of individual sources of risk will be assessed allowing to identify the key disruptors for the operation of SME’s. The relationship between the level of risk and the size of the entity will also be examined. Results: Identification of factors threatening the functioning of enterprises increases the effectiveness of risk management that accompanies the conducted activity. Empirical research allowed to recognize the most important categories and the main sources of risk associated with SME activities. The dependency between risk categories and the size of the business was confirmed, with the strength of this relationship being moderate at best.